Islamic-Based Digital Ethics: The Phenomenon of Online Consumer Data Security - Afriyan Arya Saputra; Muhammad Iqbal Fasa; Diana Ambarwati (Share: Jurnal Ekonomi dan Keuangan Islam, 2022)
This paper seeks to explain the problem of widespread consumer data theft and the significance of online consumer data privacy in a review of Islamic values-based digital ethics. This research employs a qualitative approach by reviewing a variety of books, journals, papers, and other reputable sources, which are then examined using content analytic tools. The findings of this research indicate that first and foremost, effective cybersecurity will secure customer data. Second, ethical conduct derived from Islamic beliefs will be able to deter criminal activity and data breaches against consumers. Data privacy is a fundamental right that must be maintained collectively, according to Islam. The key to combating crime and breaches in the digital environment is hence the precautionary principle of stakeholders.==========================================================================================================ABSTRAK – Etika Digital Berbasis Islam: Fenomena Keamanan Data Konsumen Online. Penelitian ini bertujuan untuk menjelaskan fenomena maraknya pencurian data konsumen serta melihat posisi penting privasi data konsumen online dalam tinjauan etika digital berbasis nilai Islam. Penelitian ini menggunakan metode kualitatif, dengan menelaah berbagai literatur baik buku, jurnal, laporan dan sumber reliable lainnya yang kemudian dianalisis menggunakan teknik content analysis. Hasil penelitian ini menemukan bahwa, pertama, keamanan siber yang baik akan mampu melindungi data konsumen. kedua, perilaku etis yang bersumber dari nilai Islam akan mampu mencegah kejahatan dan pelanggaran data konsumen. Ketiga, dalam Islam data privasi merupakan hak dasar yang harus dihormati secara bersama-sama. Untuk itu prinsip kehati-hatian daripara stakeholder menjadi kunci melawan kajahatan dan pelanggaran diruang digital.